2020
DOI: 10.1093/sleep/zsaa175
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration regularity, but not sleep duration, is associated with microvascular function in college students

Abstract: Study Objectives Vascular dysfunction is a hypothesized mechanism linking poor sleep habits to an increased incidence of cardiovascular diseases. However, the vascular profile associated with free-living sleep duration and sleep regularity has not been well elucidated, particularly in young adults. Thus, this study aimed to evaluate the associations between mean sleep duration, regularity in sleep duration, and peripheral vascular function in young adult college students. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 79 publications
2
23
1
Order By: Relevance
“…Although the emerging evidence collected in this review shows an association between intraindividual day-to-day deviations in the dura- [26]. On a positive note, most studies reviewed herein did record actigraphy data for 7 [32, 33, 46-49, 62, 69, 71, 73, 75, 77, 84, 87, 90] to 14 [85] days, as suggested by Fischer and colleagues [26]. Future studies should analyze their parameters and select the most accurate generalizable metric (or metrics) to understand which is most predictive for obesity, cardiovascular, and metabolic outcomes.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although the emerging evidence collected in this review shows an association between intraindividual day-to-day deviations in the dura- [26]. On a positive note, most studies reviewed herein did record actigraphy data for 7 [32, 33, 46-49, 62, 69, 71, 73, 75, 77, 84, 87, 90] to 14 [85] days, as suggested by Fischer and colleagues [26]. Future studies should analyze their parameters and select the most accurate generalizable metric (or metrics) to understand which is most predictive for obesity, cardiovascular, and metabolic outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…Evidence also suggests that sleep variability directly affects the vascular system, as Hoopes and colleagues examined the association between sleep variability on peripheral vascular function in 51 healthy young adults [85]. Their research showed that sleep variability is associated with poorer microvascular function, even after adjusting for sex, BMI, blood pressure, physical activity, average sleep duration, and alcohol and caffeine use [85]. More specifically, those individuals who were categorized as having high sleep variability (after researchers conducted a median split) experienced 45% less robust passive leg movement (which is a marker of resistance artery microvascular function) compared with those with low sleep variability [85].…”
Section: Sleep Variability and Cardiometabolic Health In Adolescencementioning
confidence: 99%
See 1 more Smart Citation
“…A recent mendelian randomization analysis indicated that there is a U-shaped effect of sleep duration on CVD based on data collected from 404,044 UK Biobank participants ( 33 ). Another US study showed that irregular sleep duration is associated with poorer microvascular health in young college students ( 34 ). It should be noted that inappropriate sleep patterns can also elevate the risk of CVD among young adults, which should have the lowest risk for CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, irregular sleep-wake patterns have been independently linked to cardiometabolic morbidities and risk factors including metabolic syndrome ( Huang and Redline, 2019 ), hypertension ( Brindle et al., 2019 ), adiposity ( Ogilvie et al., 2016 ), and insulin resistance ( Taylor et al., 2016 ) in midlife or later. Albeit less frequently examined, youth and young adults with irregular sleep patterns also tend to have poorer cardiometabolic health, such as increased adiposity ( Nicholson et al., 2020 ; He et al., 2015 ), impaired microvascular function, ( Hoopes et al., 2021 ) and poorer diet ( Ogilvie et al., 2018 ) when compared to those with regular sleep patterns. Our findings also parallel two studies reporting independent associations between sleep duration SD and elevated C-reactive protein in children ( Nielsen et al., 2016 ) and adolescents ( Park et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%